Healthcare Needs of U.S. Rural Latinos - Cristina Maria Figueroa; Alexandra Medvin; Boondaniwon D. Phrathep; Chad W. Thomas; Judith Ortiz; Angeline Bushy (Rural Nurse Organization; Binghamton University, 2021)
Purpose: From 2000 to 2050, the Latino population in the United States (U.S.) is expected to grow by 273%. Health outcomes vary widely among Latino subgroups and health disparities more adversely affect rural residents. The commonly used "one-size-fits-all" approach assumes that the U.S. Latino population is homogeneous. Sample, Method: Rural Latinos in four study states: Arizona (AZ), California (CA), Florida (FL) and Texas (TX) were the focus of this study. This research describes changes in the Latino population in rural counties of the U.S. in two dimensions: 1) change in population by number, and 2) change in population by country of origin using data from 2000-2017. Findings: The following themes emerged: 1) the overall Latino population grew in each state; 2) rural Latino populations in each state also increased but at a higher rate; 3) there is a variety of diversity in the countries of origin of rural Latinos based in each state; and 4) a considerable proportion of Latinos living in rural areas are of unknown Latino origins. Conclusions: As the largest racial or ethnic minority in rural populations and as the second largest group in the nation, Latino health has a significant influence on the U.S. healthcare system. For nurses, evidence-based strategies can be tailored to address diverse Latino subpopulations to reduce specific disparities for various ethnic populations. Keywords: nursing, cultural competence, Latino health, Hispanics, rural health, treatment barriers DOI: https://doi.org/10.14574/ojrnhc.v21i1.658